Knowledge and Behaviors of Veterinary Students about Rabies: A Descriptive Study from Turkey - Pirincci, E.; Kurt, O.; Oguzoncul, A. F.; Deveci, S. E. (Wolters Kluwer Medknow Publications, 2020)
Aims: This study aimed to obtain data on the knowledge, behavior, and immunization status of veterinary students about rabies. Methods and Materials: The population of this descriptive study consisted of all the 770 students of a veterinary faculty (response rate 85.7%; n = 660). A survey was conducted querying the knowledge and behaviors of the participants about rabies. Results: Of the surveyed students 28.6% (n = 189) stated that they were exposed to animal bites at least once, and 50.3% (n = 95) of these students stated that they were vaccinated following the exposure. Of the participants, 23.6% (n = 156) indicated that they received protective rabies treatment (prophylactic vaccination). About 32.9% (n = 217) of the students taking part in the study had pets at home. Around 70.7% (n = 153) of these students stated that their animals were vaccinated against rabies. A significant relationship was found between having a pet and being bitten by an animal (P < 0.001). 50.5% (n = 333) of the students who participated in the study were competent in knowledge, while 48.3% were competent in behavior. Students competent in knowledge or behavior were considerably more in the clinical classes compared to preclinical classes. A significant relationship in favor of men was found between the sexes concerning both knowledge and behavior levels. Conclusions: The study revealed deficiencies in the students' awareness levels regarding rabies. Ascertaining a sufficient amount of theory and practice courses on rabies in the veterinary faculty curriculum, starting from earlier classes will contribute to the knowledge and behaviors of the students.
Keywords: Behavior; knowledge; rabies; student; veterinary faculty